Sterno-bronchial fistula – an extremely rare complication after coronary artery bypass grafting - Nowicki, Rafał; Marczak, Jakub; Stachurski, Andrzej; Kustrzycki, Wojciech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
The incidence of complications following temporary epicardial pacing wires implantation remains low. Although rare, their late results may be unfavorable for the long-term operative outcome. The authors present a case of a 53-year-old male who developed a deep peristernal infection complicated by the formation of a sterno-bronchial fistula. Diagnosis, course, and possible causative factors are discussed. Retention of epicardial pacing wires as well as lung pleura laceration due to inadvertent metallic suture handling may play a role in the formation of sterno-bronchial fistula. We recommend a classic fistulography, with a simple drain fixed in the entry of the skin fistula as a route to administer the contrast medium, the diagnostic tool of choice while considering the above diagnosis.